Self-Regulation in Primary School - García Gaitero, Óscar (Rastros Rostros, 2014)
Most research studies on self-regulated learning have been conducted with students in secondary andhigher education, forgetting that primary school students are the ones who may face the most problemswhen cognitive and metacognitive strategies are applied. This article highlights the importance oftraining children how to self-regulate their learning as they start their studies. In these first crucial years,students learn and develop attitudes of self-sufficiency that are easier to change than when they havealready developed and consolidated learning styles
Keywords: efficient students; self-regulated learning; active learning; cognitive; development; paradigm